2004
DOI: 10.1089/154099904323087105
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Cardiovascular Risk Factors in Postmenopausal Women through a Lifestyle Change Intervention

Abstract: Lifestyle change interventions may be an effective means for reducing cardiovascular risk in obese, sedentary, postmenopausal women. However, greater attention should be devoted to the maintenance of these positive lifestyle changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 78 publications
8
45
1
5
Order By: Relevance
“…The decrease in body weight (and thus BMI) and fat mass found in both groups of our study is in good agreement with the reduction in adiposity previously observed in obese women subjected to weight reducing programs combining aerobic exercise and dietary restriction [36][37][38]. The fact that our participants lost a similar fat mass as women subjected to long-term (3-to 6-month) weight reducing programs with comparable [38] or less rigid caloric restriction [36,37] indicates that short-term low-intensity physical activity associated with caloric restriction seems to be sufficient to promote body weight loss in women with different obesity degrees. Furthermore, the lean mass decrease of 13% seen after the short-term weight reducing program in all women is lower than that noted at the same time of long-term (lasting from 9 to 16 weeks) very-low-or low-caloric diet studies [39].…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in body weight (and thus BMI) and fat mass found in both groups of our study is in good agreement with the reduction in adiposity previously observed in obese women subjected to weight reducing programs combining aerobic exercise and dietary restriction [36][37][38]. The fact that our participants lost a similar fat mass as women subjected to long-term (3-to 6-month) weight reducing programs with comparable [38] or less rigid caloric restriction [36,37] indicates that short-term low-intensity physical activity associated with caloric restriction seems to be sufficient to promote body weight loss in women with different obesity degrees. Furthermore, the lean mass decrease of 13% seen after the short-term weight reducing program in all women is lower than that noted at the same time of long-term (lasting from 9 to 16 weeks) very-low-or low-caloric diet studies [39].…”
Section: Discussionsupporting
confidence: 92%
“…Ten studies [25,32,36,45,46,[53][54][55][56]58] allowed the investigation of an intensive against a less intensive D-PA intervention. None of these studies reported significant differences between groups for kilocalorie intake at any point in time.…”
Section: Weight Change Diet and Pa Interventions Versus Waiting List mentioning
confidence: 99%
“…Intensive versus Less Intensive Interventions: 11 studies [19,25,32,36,46,47,[53][54][55][56][57] allowed comparisons between intensive and less intensive interventions at various points in time. Intensive interventions, irrespective of whether the intervention consisted of a D-only or D-PA intervention, tended to induce greater MD for weight than the less intensive intervention groups (table 3).…”
Section: Weight Change Diet and Pa Interventions Versus Waiting List mentioning
confidence: 99%
“…This gap must be addressed to ensure the effectiveness of current obesity intervention to these groups. In previous studies, lifestyle interventions including physical activity, diet modification and smoking cessation have dominated research interest following convincing findings (6)(7)(8). Additionally, studies have found that sedentary populations adhere better to lifestyle intervention with accumulated bouts of activity compared to structured exercises (9).…”
Section: Intervention and Control Group Taskmentioning
confidence: 99%